2020
DOI: 10.1080/03004279.2020.1809489
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ perceptions of successful transition to school for children with and without Downs Syndrome in the UAE and England

Abstract: Teachers' perceptions of successful transition to school for children with and without Downs Syndrome in the UAE and England.The experience of transition into school has been shown to correlate with later school outcomes, with a successful experience resulting in later positive academic and social outcomes. Children with Special Educational Needs (SEN) face more challenging transitions. Teacher attitudes and expectations of children with SEN play a key role in determining the quality of the transition. Early Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…Ring et al (2016) found that teachers placed great emphasis on children being socially and emotionally ready for school, being able to follow routines, being independent and, crucially, having good communication skills. Similarly, studies of teacher expectations in the UAE revealed a similar pattern of importance being placed on new starters being emotionally mature (Takriti, Elhoweris & Atkinson, 2018;Takriti, Atkinson & Elhoweris, 2019;Takriti, 2019;Atkinson, Takriti & Elhoweris, 2020). Parker and Neuharth-Pritchett (2006) and O'Kane and Hayes (2013) found that teachers perceived that early years' provision is becoming more academic and there is a need to focus more on academic skills alongside social competence.…”
Section: Sub-theme 2: Talking Is a Successful Transitionmentioning
confidence: 90%
“…Ring et al (2016) found that teachers placed great emphasis on children being socially and emotionally ready for school, being able to follow routines, being independent and, crucially, having good communication skills. Similarly, studies of teacher expectations in the UAE revealed a similar pattern of importance being placed on new starters being emotionally mature (Takriti, Elhoweris & Atkinson, 2018;Takriti, Atkinson & Elhoweris, 2019;Takriti, 2019;Atkinson, Takriti & Elhoweris, 2020). Parker and Neuharth-Pritchett (2006) and O'Kane and Hayes (2013) found that teachers perceived that early years' provision is becoming more academic and there is a need to focus more on academic skills alongside social competence.…”
Section: Sub-theme 2: Talking Is a Successful Transitionmentioning
confidence: 90%
“…Selecting criteria are (a) being in the library collection, (b) being published in a peer-reviewed academic journal, (c) in English and (d), at least one participant is a disadvantage. The concept of transition to school is handled in different ways in research (Atkinson et al, 2021;Helm et al, 2019), but in this study, as mentioned in the introduction part, it is considered as Grade 1 since it symbolizes the transition to a formal approach in the current education system. Therefore, pre-school education, or reception class is excluded.…”
Section: Electronic Screeningmentioning
confidence: 99%
“…Furthermore, it appears that when developing the individual educational program, teachers are more willing to support the benefits of inclusion when they believe and trust in the success that will be achieved by children with DS in their class group. The authors of a study aimed at analyzing teachers’ perceptions [ 15 ] of the successful transition from kindergarten to primary school for children with and without DS state that the former may need support and adjustments; however, if initial expectations of the teacher are lower for children with DS than for children without disabilities, then it is probable that the gap between the two groups, which emerged at school entrance, will increase more and more over time. In the same study, the factors that they consider most important to allow children with DS to achieve good performance, concern aspects related to how much the child is willing to go to school and how much they manage to adapt within the classroom.…”
Section: Introductionmentioning
confidence: 99%